The Inclusive Professional Framework for Societies: Changing Mental Models to Promote Diverse, Equitable, and Inclusive STEM Systems Change - Leibnitz, Gretalyn M.; Gillian-Daniel, Donald L.; Greenler, Robin M c C.; Campbell-Montalvo, Rebecca; Metcalf, Heather; Segarra, Verónica A.; Peters, Jan W.; Patton, Shannon; Lucy-Putwen, Andrea; Sims, Ershela L. (Frontiers in Sociology, 2022)
Science, technology, engineering, and mathematics (STEM) professional societies (ProSs) are uniquely positioned to foster national-level diversity, equity, and inclusion (DEI) reform. ProSs serve broad memberships, define disciplinary norms and culture, and inform accrediting bodies, thus providing “excellent leverage with which to design and promote change” (National Academy of Sciences et al., 2005). ProSs could be instrumental in achieving the DEI system reform necessary to optimize engagement of all STEM talent, leveraging disciplinary excellence resulting from diverse teams. Inclusive STEM system reform requires that underlying “mental models'' be examined (e.g., Kania et al., 2018). The Inclusive Professional Framework for Societies (IPF:Societies) is an interrelated set of strategies that can help ProS change leaders (i.e., “Boundary Spanners'”) and organizations identify and address mental models hindering DEI reform. The IPF:Societies uses four “I’s”—Identity awareness and Intercultural mindfulness (i.e., equity mindset) upon which Inclusive relationships and Influential DEI actions are scaffolded. We discuss how the IPF:Societies complements existing DEI tools [e.g., Women in Engineering ProActive Network’s Framework for Promoting Gender Equity within Organization; Amplifying the Alliance to Catalyze Change for Equity in STEM Success’ Equity Environmental Scan Tool (Peters et al., 2021)]. We explain how the IPF:Societies can be applied to existing ProS policy and practice associated with common ProS functions (e.g., leadership, membership, conferences, awards, and professional development). Next steps are to pilot the IPF:Societies with a cohort of STEM ProSs. Ultimately, the IPF:Societies has potential to promote more efficient, effective, and lasting DEI organizational transformation, and contribute to inclusive STEM disciplinary excellence.